Bacteriocinogenic Lactococcus lactis subsp: lactis DF04Mi isolated from goat milk: Evaluation of the probiotic potential - Furtado,Danielle N. (2014)
Lactic acid bacteria capable of producing bacteriocins and presenting probiotic potential open innovative technological applications in the dairy industry. In this study, a bacteriocinogenic strain (Lactococcus lactis subsp. lactis DF4Mi) was isolated from goat milk, and studied for its probiotic potential. Lc. lactis DF4Mi was resistant to acidic pH and oxbile, presented co-aggregation with Listeria monocytogenes, and was not affected by several drugs from different generic groups, being sensitive to most tested antibiotics. These properties indicate that this Lc. lactis strain can be used for enhancement of dairy foods safety and quality, in combination with potential probiotic properties.